2010
DOI: 10.1242/jcs.061978
|View full text |Cite
|
Sign up to set email alerts
|

E1^E4-mediated keratin phosphorylation and ubiquitylation: a mechanism for keratin depletion in HPV16-infected epithelium

Abstract: SummaryThe keratin IF network of epidermal keratinocytes provides a protective barrier against mechanical insult, it is also a major player in absorbing stress in these cells. The human papilloma virus (HPV) type 16 E1^E4 protein accumulates in the upper layers of HPV16-infected epithelium and is known to associate with and reorganise the keratin IF network in cells in culture. Here, we show that this function is conserved amongst a number of HPV alpha-group E1^E4 proteins and that the differentiation-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 55 publications
1
33
1
6
Order By: Relevance
“…Analysis of both 16E1 E4 and keratin 18 patterns showed that treatment with calpain inhibitor III significantly reduced the degree of reorganization at both time points. Compared to previous reports of 16E1 E4-associated reorganization in cell culture (13,22), reorganization occurring at relatively early time points in our system, which we think is partly a function of the cell line that we are using but mostly because the necessary control addition of DMSO, which has been found to greatly increase the expression levels of 16E1 E4 in transient-transfection experiments (data not shown). At 16 h, in cells treated with DMSO, the majority of the 16E1 E4 networks are in the middle or late stages of reorganization.…”
Section: Vol 85 2011 Calpain Cleavage Of 16e1 E4 and Effects On Kercontrasting
confidence: 85%
“…Analysis of both 16E1 E4 and keratin 18 patterns showed that treatment with calpain inhibitor III significantly reduced the degree of reorganization at both time points. Compared to previous reports of 16E1 E4-associated reorganization in cell culture (13,22), reorganization occurring at relatively early time points in our system, which we think is partly a function of the cell line that we are using but mostly because the necessary control addition of DMSO, which has been found to greatly increase the expression levels of 16E1 E4 in transient-transfection experiments (data not shown). At 16 h, in cells treated with DMSO, the majority of the 16E1 E4 networks are in the middle or late stages of reorganization.…”
Section: Vol 85 2011 Calpain Cleavage Of 16e1 E4 and Effects On Kercontrasting
confidence: 85%
“…HPV16 E1^E4 was found to effect a dramatic cessation of keratin IF network dynamics by associating with both soluble and insoluble keratin. These observations shed new light on the mechanism of keratin IF network reorganisation mediated by HPV16 E1^E4 (McIntosh et al, 2010). E1^E4 also translocates to mitokondria via an N-terminal leucine-rich region and induces the detachment of mitocondria from microtubules.…”
Section: Wwwintechopencommentioning
confidence: 78%
“…HPV proteins are interacted with cell skeletal filaments. Some of these proteins are E6 (HPV16,18), E7 (HPV16,18,38), E5 (high and low risk HPV types), E1^E4 (HPV16), E4 proteins (Lee & Dominguez, 2010;McIntosh et al, 2010;Nguyen 2008;Rey et al, 2000, Safi Oz, 2010Stanley, 2001;Uribe & Jay., 2009;Yue et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations